MILITARY INTERVENTIONS IN THE UNIPOLARITY: LESONS FOR SECURITY DYNAMICS OF US-CHINA RELATIONS AMID TRUMP’S SECOND TERM - Stekić, Nenad (The Policy of National Security, 2025)
Humanitarian interventionism, a hallmark of the unipolar era following the Cold War, has been widely debated as a mechanism for addressing alleged human rights violations and safeguarding global security. Rooted in principles such as the Responsibility to Protect (R2P), these interventions have often intersected with the strategic interests of dominant powers, particularly the United States. This paper examines the evolving dynamics of humanitarian intervention within the shifting geopolitical landscape, focusing on the implications for US-China relations during President Donald Trump’s second term in office. Building on historical precedents and theoretical frameworks, the study analyzes how the US might invoke humanitarian intervention as a dual-purpose tool – asserting moral leadership while countering China’s growing influence in regions of strategic interest. It further explores the challenges of applying lessons from interventions in the unipolar era to a world increasingly defined by multipolarity and strategic rivalry. By contextualizing Trump’s assertive foreign policy stance and examining potential justifications for interventionism, the paper offers critical insights into how humanitarian motives might align with or mask broader geopolitical objectives. Consequently, this analysis sheds light on the security implications for US-China relations, contributing to the wider discourse on the intersection of ethics, power, and global governance.